Taco-tastic : over 60 recipes to make taco Tuesdays last all week long - Elizondo, Victoria; Ayala, Valerie (London : Oh! Life, 2022)
Increase your Taco Tuesday repertoire and take a deeper dive into the versatility of this popular mealtime treat with this collection of fun, accessible taqueria food. Specializing in vibrantly colourful, authentic Mexican fare using only fresh ingredients, chef Victoria Elizondo focuses on Mexican guisos - the type of food that makes you feel you are home.
Salsas -- Tortillas and sides -- Breakfast tacos -- Meat and poultry -- Fish and seafood -- Vegan and vegetarian -- Healthy and light -- Taco party!
All Grades
Includes index.
Keywords: Cooking, Mexican -- Juvenile literature; Tacos; Cookbooks